Determination of arsenic and lead level in blood of adults from coastal community in Melaka, Malaysia - Mohd Noor, Farrah Atiqah; Mohd Elias, Saliza; Aris, Ahmad Zaharin; Abu Bakar @ Jamaludin, Suhaili; Md Zulkifli, Hamizah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Accumulation of heavy metals through seafood consumption constitutes a significant potential threat to human health. Biomonitoring of whole blood heavy metals level gave an insight into the internal body burden to the exposure of heavy metals. The aims of this study were to assess the blood heavy metals (arsenic and lead) level among the coastal community of Melaka and to determine their association with sociodemographic background and potential sources of heavy metals accumulation. Methods: Respondents were recruited through purposive sampling technique based on inclusion and exclusion criteria. The questionnaires were distributed to obtain sociodemographic information, the frequency of seafood intake and smoking habit. Blood samples were obtained on a voluntary basis. A total of 63 respondents completed all the information required. The heavy metals concentration in blood was determined by inductively coupled plasma- mass spectrometry (ICP-MS). Results: The blood arsenic (BAs) concentration of respondents was 0.076 (0.059 – 0.107) μg/L and the blood lead (BPb) concentration of respondents was 1.204 (0.670 – 2.094) μg/L respectively. A significant association was observed between seafood-based product frequency intake and BPb concentration (p < 0.05). Other seafood frequency intake and background factors were not significantly associated with the BAs and BPb concentration of respondents. Conclusion: The findings showed that arsenic and lead levels in the blood of respondents along the coastal area of Melaka did not exceed the blood heavy metals reference levels and there was also lack of associations between blood heavy metals concentration and the potential factors of heavy metals accumulation studied.